Pengaruh Kondisi Kerja dan Stres Kerja terhadap Kualitas Kerja Karyawan pada PT. Julia Multimedia Nusantar - Nurasizah Nurasizah; M Ilham Wardhana Haeruddin; Agung Widhi Kurniawan; Abdi Akbar Idris; Andi Mustika Amin (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
The purpose of this study is to determine how stress and work environment affect employees' job quality at PT. Julia Multimedia Nusantara. This study uses a quantitative approach and has 32 respondents. Before performing a berganda regression analysis on the collected data, a kuesioner is used to ensure validity and trustworthiness. The study's findings indicate that work conditions have a significant impact on employees' work quality; better work conditions consistently raise work quality. In addition, it has been shown that stress at work has a significant and positive impact on work quality, meaning that higher stress levels are associated with higher work quality. Combining a stressful work environment with a high level of stress.